Etika Islam terhadap Kecerdasan Buatan: Telaah Prinsip Moral dan Pendekatan Maqashid Syariah - Muhammad Yasir, Aqila Azka Halmar; Pradipta, Garnis Nindya; Pohan, Irma Suryani; Jibril, Muhammad; Utami, Risyda Johannisa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The rapid development of artificial intelligence (Artificial Intelligence/AI) has brought significant impacts in various aspects of human life, ranging from education, health, security, to religion. On the back of those benefits, complex ethical issues arise, such as machine autonomy, algorithmic decision-making, privacy violations, and inequality of technological access. This article poses a critical question: how does the Islamic ethical view of this phenomenon and to what extent can the principles of maqÄá¹£id al-sharÄ«â€˜ah be a normative foundation for assessing and directing the development of AI? This study employed a normative qualitative approach with bibliographic methods against classical and contemporary literature regarding Islamic ethics, Shariah maqashid, and AI ethical issues. The results of the study indicate that the basic principles of Islamic ethicsâ€”such as taklif, justice, maslahah, ethics, and the prohibition of zulmâ€”are highly relevant for dealing with the ethical challenges posed by AI. The Shariah maqashid approach, with its five objectives (á¸¥ifáº“ al-dÄ«n, al-nafs, al-â€˜aql, al-nasl, and al-mÄl), proved to be applicative in evaluating the benefits and risks of AI technologies in various sectors. This article affirms the importance of Muslimsâ€™ role in framing AI regulation and governance based on spiritual values, social justice, and moral responsibility.